Prevalence of sedentary lifestyle, overweight and body image dissatisfaction among adolescents from Florianópolis, SC - Andreia Pelegrini (Universidade Federal de Santa Catarina, 2009)
Objective: Analyze the prevalence of sedentarism lifestyle, overweight and body image dissatisfaction among adolescents and the factors associated with these variables. Methods: This was a cross-sectional study of a representative sample of adolescents aged 14 to 18 years, enrolled in public sector Secondary Education in Florianópolis, SC, Brazil. The following data were recorded: sociodemographic (gender, age, socioeconomic status), anthropometric (body weight, height), perception of body image (real and ideal silhouettes) and level of physical activity (sedentarism lifestyle: < 300 minutes/week). Results: The prevalence of sedentarism lifestyle was 25.4% (male: 21.9%; female: 27.1%, p = 0.177). Among the females, it was found that low weight adolescents and those who spend more than 4 hours/day watching television had 2.69 and 2.25 times greater chance of being sedentary respectively. The prevalence of overweight was 13.9% (male: 13.6%; female: 14.1%, p = 0.860). There was an association between overweight and socioeconomic status, where adolescents living in better economic conditions (class A) demonstrated a 2.7 times greater chance of being overweight with relation to lower economic classes (C+D+E). The proportion of adolescents unsatisfied with body image was 65.5% (male: 72.6%; female: 61.8%, p < 0.001). The results also demonstrated that 48.4% of the female adolescents and 51.3% of the male adolescents wished to reduce or increase their body silhouettes, respectively. Unhealthy BMI was associated with body image dissatisfaction only among the girls (95%CI%=1.35-3.43). Overweight girls exhibited 11 times greater chances of body image dissatisfaction than those with healthy BMI. Conclusion: The sedentarism lifestyle among adolescents is worrying, since it affects one in every four adolescents. For this reason, physical activity programs are recommended during this stage of life. With relation to overweight, interventions with adolescents, particularly those from higher socioeconomic levels, should include nutritional guidance and encourage physical activity. Nutritional status was a decisive factor in body dissatisfaction, primarily among female adolescents, since those with unhealthy nutritional status had higher levels of dissatisfaction than those with healthy BMI.